2013
DOI: 10.11138/ccmbm/2013.10.1.019
|View full text |Cite
|
Sign up to set email alerts
|

The genetic profile of bone repair

Abstract: SummaryBone repair following a fracture is a complex, well orchestrated, physiological process in response to injury. Even though the exact number of the genes and expressed proteins involved in fracture healing remains unknown, the molecular complexity of the repair process has been demonstrated, and it involves numerous genes and molecules, such as extracellular matrix genes, growth and differentiation factors, matrix metalloproteinases, angiogenic factors and others. Discrepancies in fracture healing respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous gene studies in bone healing suggest the molecular complexity of the repair process, with almost 600 known genes and over 100 novel genes. 14 And while specific elements of classic canonical bone formation pathways such as Wnt/betacatenin 15,16 and BMP 17,18 have been studied as a function of aging fracture healing, they have not been evaluated together within the context of global gene expression nor have they been well studied in very old (rather than moderately aged) mice. Moreover, there has not been a transcriptome-level analysis of fracture healing in aged mice.…”
mentioning
confidence: 99%
“…Previous gene studies in bone healing suggest the molecular complexity of the repair process, with almost 600 known genes and over 100 novel genes. 14 And while specific elements of classic canonical bone formation pathways such as Wnt/betacatenin 15,16 and BMP 17,18 have been studied as a function of aging fracture healing, they have not been evaluated together within the context of global gene expression nor have they been well studied in very old (rather than moderately aged) mice. Moreover, there has not been a transcriptome-level analysis of fracture healing in aged mice.…”
mentioning
confidence: 99%
“…Potential targets of these investigations in fracture repair studies are vast, including genes related to the extracellular matrix, growth and differentiation factors, matrix metalloproteinases, and angiogenic factors. 78 Hadjiargyrou et al have identified 704 genes of particular significance to the fracture repair process. 79 Fracture healing investigations often utilize qRT-PCR, RNA sequencing, and reporter mice to study the role of these genes in the molecular and cellular processes of fracture repair.…”
Section: Discussionmentioning
confidence: 99%
“…In general, RNA sequencing involves isolation and purification of RNA followed by fragmentation and reverse transcription to generate complementary DNA (cDNA). Sequencing adapters are then ligated to the ends of these fragments, and they are read by a sequencing platform 78. scRNA involves additional considerations for capturing single cells and unbiased cDNA amplification 79.…”
mentioning
confidence: 99%
“…Collectively, these events involve a large number of secreted signaling messengers that activate signaling pathways leading to differential expression of a large number of genes, ultimately resulting in progenitor cell proliferation and differentiation leading to repair of fractured bone [ 9 ]. Genetic studies on bone healing demonstrate the molecular complexity of the repair process, with nearly 600 known genes and more than 100 novel genes [ 10 ]. A direct comparison of the fracture healing process with the gene expression changes without fracture may provide more insight.…”
Section: Introductionmentioning
confidence: 99%